Assessment of Background Hydrogen by the Monte Carlo Computer Code MCNP-4A during Measurements of Total Body Nitrogen - RYDE, S. J. S.; AL-AGEL, F. A. M.; EVANS, C. J.; HANCOCK, D. A. (Annals of the New York Academy of Sciences, 2000)
: The use of a hydrogen internal standard to enable the estimation of absolute mass during measurement of total body nitrogen by in vivo neutron activation is an established technique. Central to the technique is a determination of the H prompt gamma ray counts arising from the subject. In practice, interference counts from other sources‐e.g., neutron shielding‐are included. This study reports use of the Monte Carlo computer code, MCNP‐4A, to investigate the interference counts arising from shielding both with and without a phantom containing a urea solution. Over a range of phantom size (depth 5 to 30 cm, width 20 to 40 cm), the counts arising from shielding increased by between 4% and 32% compared with the counts without a phantom. For any given depth, the counts increased approximately linearly with width. For any given width, there was little increase for depths exceeding 15 centimeters. The shielding counts comprised between 15% and 26% of those arising from the urea phantom. These results, although specific to the Swansea apparatus, suggest that extraneous hydrogen counts can be considerable and depend strongly on the subject's size.